Prospecção de bactérias produtoras de amilases para sacarificação de microalgas - Santos, Marilda Ferreira dos (2018)
Research related to the production processes of biofuels through microalgae called third generation biofuels are gaining space in the world due to their greater sustainability, since they do not compete directly with the production of food by arable areas. Spirulina platensis is a microalgae whose chemical composition is known, with considerable potential for the production of biofuels. For the process to be viable it is necessary that the carbohydrates present in the microalga are transformed into fermentable sugars, and the hydrolysis of the microalgae biomass can be carried out in a chemical or enzymatic way. Enzymatic hydrolysis is considered to be a more convenient process compared to other methods, since enzymes produced by microorganisms such as fungi and bacteria can be used. Numerous microorganisms are in soil and water, presenting specific and distinct characteristics, according to the conditions and nutrients available to develop. The objective of this work was to select bacteria that produce specific amylolytic enzymes for the hydrolysis of the carbohydrates of the Spirulina platensis microalgae. The research began in the study of the microalgae chemical pre-treatment, adaptation, growth and identification of the microorganisms, the production of enzymatic extract, characterization and application in the microalga Spirulina platensis. In relation to the pre-treatments the ones that made the most carbohydrates were acid pre-treatment at 6% concentration, releasing about 60% carbohydrates and 12% alkali pre-treatment, providing 50% carbohydrates contained in the microalga. From the Winogradsky columns used for the development of amylolytic bacteria, from 45 isolated colonies, 97% had amylolytic characteristics, and 10 bacteria with a higher amylolytic potential were selected qualitatively. These were submitted to fermentation for 7 days for the production of enzymes, being selected 4 bacteria with higher enzymatic activity in a shorter incubation time. The crude enzymatic extracts showed to be thermostable, 2 with residual enzymatic activity above 60% at 95 ° C. The extracts were evaluated in different pH conditions, being that at pH 5.5 and 6.5 they obtained residual activity superior to the others evaluated. Respectively the crude and purified enzymatic extracts underwent evaluations of electronic transitions and vibrational transitions demonstrating molecules constituent of proteins and that they had similar organic composition. The crude and purified enzymatic extracts were evaluated in biomass Spirulina platensis for a period of 48h and one of the extracts obtained 1.67 g / L of reducing sugars in 24 h. It is concluded that the extracts obtained have amylolytic potential in the biomass as well as in starch, demonstrating a thermostable character at high temperatures, even making these enzymes suitable for different uses, not only for saccharification of microalgae.